Customer Satisfaction, Revisit Intention and Promoting Ferry Transportation - Hafiludin Usman; Andhik Kanitra; Anita Maharani (Journal of Business and Management Review, 2020)
This study aims to prove the research model about the relationship between customer satisfaction, revisit intention and words of mouth. The literature review used begins with marketing management, then the dynamics between the variables raised. The research method chosen is a quantitative approach; the object of this research is at the Hunimua-Waipirit port, Maluku, Indonesia, and with a research sample of 75 people, then analyzed using SMART PLS. The results obtained indicate that customer satisfaction, words of mouth and revisit intention are related to one another. Customer satisfaction will affect revisit intention, customer satisfaction will affect words of mouth, and words of mouth affect revisit intention.